Sermons Preached in India - Heber, Reginald (Cambridge library collection. Religion, 1829)
Reginald Heber (1783–1826), second bishop of Calcutta, was appointed to the role in 1823, and had for a long time been interested in the Church of England's overseas missions. His diocese in the subcontinent had been established less than a decade before, in 1814, and included India, southern Africa and Australia. Heber travelled extensively throughout, visiting remote Anglican communities and later publishing journals about his travels. In addition, he was well-known as a hymn-writer. Sermons Preached in India, however, was published posthumously in 1829, and edited by his widow, Amelia. This volume also illustrates Heber's zeal to carry out his work across his diocese, the location of his sermons range from Delhi to Dum Dum. Missionaries would have been a significant part of his diocese, and these homilies reflect many of the difficulties faced by Anglicans living in a place that had its own strong religious beliefs